2016
DOI: 10.1124/mol.116.104018
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Subcellular Dynamics of Sigma-1 Receptor Mutants Underlying Neuromuscular Diseases

Abstract: The sigma-1 receptor (s-1R) is an endoplasmic reticulum resident chaperone protein involved in a plethora of cellular functions, and whose disruption has been implicated in a wide range of diseases. Genetic analysis has revealed two s-1R mutants involved in neuromuscular disorders. A point mutation (E102Q) in the ligand-binding domain results in the juvenile form of amyotrophic lateral sclerosis (ALS16), and a 20 amino-acid deletion (D31-50) in the putative cytosolic domain leads to a form of distal hereditary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
29
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 87 publications
7
29
1
Order By: Relevance
“…; Wong et al. ). In this work, we show that Sig‐1R activation by SKF inhibits Kv1.2, as observed for other Kv1.x subtypes (Aydar et al.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…; Wong et al. ). In this work, we show that Sig‐1R activation by SKF inhibits Kv1.2, as observed for other Kv1.x subtypes (Aydar et al.…”
Section: Discussionmentioning
confidence: 98%
“…, , ; Wong et al. ). Additionally, it has been shown that the Sig‐1R can translocate to the nuclear envelope upon activation with cocaine, and it has also been reported that the Sig‐1R may reside in the PM in dorsal root ganglion (DRG) neurons (Mavlyutov et al.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations